Toshio Shibata - Japan - Prodger, Phillip 1967- (Prestel, 2023)
Spanning the career of one of Japan’s most revered photographers, this monograph—the only English-language volume of its kind—features exquisitely detailed full-page images that capture the relationship between human-made structures and the natural world. Toshio Shibata’s large-format contemporary landscapes are distinguished by their haunting beauty, graceful composition, and meticulous detail. Using long exposures, and eliminating any references to people, horizons, or identifying geographic reference points, Shibata captures structures such as dams, bridges, reservoirs, and roads as they interact with their natural settings—mountainsides, rivers, and forests and fields. The results are highlighted by painterly composition; filled with patterns, lines, and fluid action; and unmistakably Japanese in their aesthetic. Curated and with commentary by Phillip Prodger, one of the most erudite and critical voices in contemporary photography, this book will appeal both to fans of Shibata’s work as well as an audience that has yet to discover his remarkable oeuvre
Keywords: Shibata, Toshio -- 1949-; Naturfotografie; Fotografie; Landschaftsfotografie; Architekturfotografie; Japan; Bildband